Lateral release of proteins from the TOM complex into the outer membrane of mitochondria - Harner, Max; Neupert, Walter; Deponte, Marcel (The EMBO journal, 2011)
The TOM complex mediates import of mitochondrial proteins. Here, this complex is also shown to promote lateral release of proteins into the outer membrane